2008
DOI: 10.1002/jbm.b.31197
|View full text |Cite
|
Sign up to set email alerts
|

MBG/PLGA composite microspheres with prolonged drug release

Abstract: Mesoporous bioactive glass (MBG) and composite microspheres with MBG particles embedded in biodegradable poly(D,L-lactide-co-glycolide) (PLGA) matrix have been prepared and used to load gentamicin (GS). The in vitro drug release experiments from both MBG and composite microspheres were conducted in distilled water and phosphate buffered saline (PBS) solution at 37 degrees C for more than 30 days. In both water and PBS, GS release from the MBG was very fast with about 60 wt % of the loaded drug released in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…MBG has significantly different dissolution compared with NBG and HAp, and the drug-loading and release kinetics of alginate microspheres can effectively be controlled by their dissolution of the inorganic ions [42]. By incorporating MBG future science group into poly(lactic-co-glycolic acid) (PLGA) microspheres, Li et al produced a composite system with a slower release kinetic than pure MBG and a more sustained drug delivery [43]. A novel dual-drug delivery system based on MBG/polypeptide graft copolymer nanomicelle composites was loaded with water-soluble gentamicin and fat-soluble naproxen.…”
Section: Mbg Compositesmentioning
confidence: 97%
“…MBG has significantly different dissolution compared with NBG and HAp, and the drug-loading and release kinetics of alginate microspheres can effectively be controlled by their dissolution of the inorganic ions [42]. By incorporating MBG future science group into poly(lactic-co-glycolic acid) (PLGA) microspheres, Li et al produced a composite system with a slower release kinetic than pure MBG and a more sustained drug delivery [43]. A novel dual-drug delivery system based on MBG/polypeptide graft copolymer nanomicelle composites was loaded with water-soluble gentamicin and fat-soluble naproxen.…”
Section: Mbg Compositesmentioning
confidence: 97%
“…Thus, composite materials combining a mesoporous particle and a biodegradable polymeric phase were developed to mimic the major ECM of bone; they combine the advantages and minimize the drawbacks of each material in the composite . For example, Shi et al showed that the addition of mesoporous bioactive glasses (MBG) into poly( l ‐lactic acid) (PLLA) resulted in enhanced cell attachment with cell spreading and proliferation in a rabbit bone marrow stromal cells (rBMSCs) model . Wu et al fabricated multifunctional porous MBG scaffolds with osteostimulation, drug delivery, and antibacterial properties …”
Section: Type Of Applicationsmentioning
confidence: 99%
“…57 For example, Shi et al showed that the addition of mesoporous bioactive glasses (MBG) into poly(L-lactic acid) (PLLA) resulted in enhanced cell attachment with cell spreading and proliferation in a rabbit bone marrow stromal cells (rBMSCs) model. 58 Wu et al fabricated multifunctional porous MBG scaffolds with osteostimulation, drug delivery, and antibacterial properties. 59 Bone morphogenic protein-2 (BMP-2) is considered as one of the most effective and extensively used growth factor to induce osteoblast differentiation and accelerate bone regeneration.…”
Section: Type Of Applicationsmentioning
confidence: 99%
“…Improved tensile modulus and tensile strength were obtained, but the composites appeared rather brittle . Shi and co‐workers showed that the addition of mesoporous bioactive glass into PLLA matrix enhanced the cell attachment, resulting in cell spreading and proliferation in a rabbit bone marrow stromal cells model …”
Section: Introductionmentioning
confidence: 99%
“…23 Shi and co-workers showed that the addition of mesoporous bioactive glass into PLLA matrix enhanced the cell attachment, resulting in cell spreading and proliferation in a rabbit bone marrow stromal cells model. 24 In this work, SBA-15 particles were first surface modified using APTES as coupling agent to introduce ammonium groups, followed by grafting of PLLA short chains on the surface through ammonium initiated ring-opening polymerization of L-lactide. Composites of a PLTG matrix reinforced by surface modified SBA-15 with various filler contents were then prepared via solution mixing of both components.…”
mentioning
confidence: 99%